PENGARUH LITERASI KEUANGAN, FINANCIAL SELF EFFICACY DAN TEKNOLOGI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA DI YOGYAKARTA - Perkasa, Tito Pramudya Wahyu; Retnaningdiah, Dian (Program Studi Manajemen, 2023)
Having good financial behavior has a positive impact on students regarding their financial problems, especially in managing expenses for daily needs. Financial literacy, financial self-efficacy, and financial technology are parts that can provide convenience to students in overcoming their financial problems. Purpose: This study aims to determine the effect of financial literacy, financial self-efficacy, and financial technology on the financial behavior of students in Yogyakarta. Research Methods: This study used a descriptive quantitative method, the sample used was 50 boarding/contract/living alone students in Yogyakarta. The instrument used is a questionnaire. Test the validity of the instrument using R count and R table, while the Reliability Test uses Crombach alpha. The data analysis technique used is the Classical Assumption Test, Multiple Linear Regression Test, Partial Test (t), Simultaneous Test (f), and Determination Test (R2). Research Results: The results obtained after data analysis are significantly Financial Literacy (X1) and Financial Technology (X3) have no effect on student financial behavior (Y). Meanwhile, Financial Self Efficacy (X2) has a significant effect on financial behavior (Y). Simultaneously financial literacy (X1), financial self-efficacy (X2), and financial technology (X3) influence financial behavior (Y).